2016
DOI: 10.4209/aaqr.2015.07.0470
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation, Sources and Transport of Aerosols at Lijiang, Southeast Tibetan Plateau

Abstract: Aerosol samples were collected during pre-monsoon, monsoon and post-monsoon periods in 2009 in Lijiang, a tourism city located on the southeast Tibetan Plateau, southwest China. To determine the seasonal variation and sources of aerosol species, main elements and water soluble ions were analyzed. The results showed that crustal elements (Si, K, Ca, Ti and Fe) were the main elements with an enrichment whose enrichment factor (EF) value were lower than 10, with the large value (except Ca) occurring during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Similarly, over the southeast Tibetan Plateau, Zhang et al . [] have reported that the largest values of UVAI appeared at south edge of Tibetan Plateau (TP) and western China. Based on the modeling study on transport of summer dust and anthropogenic aerosols over the Tibetan Plateau, Liu et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, over the southeast Tibetan Plateau, Zhang et al . [] have reported that the largest values of UVAI appeared at south edge of Tibetan Plateau (TP) and western China. Based on the modeling study on transport of summer dust and anthropogenic aerosols over the Tibetan Plateau, Liu et al .…”
Section: Resultsmentioning
confidence: 98%
“…The May aerosol index increased from about 2.5 before 1993 to about 4 in 2000 and more than 11 in 2003. Similarly, over the southeast Tibetan Plateau, Zhang et al [2016] have reported that the largest values of UVAI appeared at south edge of Tibetan Plateau (TP) and western China. Based on the modeling study on transport of summer dust and anthropogenic aerosols over the Tibetan Plateau, Liu et al [2015] have also reported the presence of highly absorbing aerosols around the Taklimakan desert, the southern slope, and the area east of the TP based on the high values of AI.…”
Section: Uv-aerosol Index From Ozone Monitoring Instrumentmentioning
confidence: 92%
“…As previously discussed, both regions are characterized by natural aerosols. In the western Sichuan Plateau, the increasing aerosol loading during the rainy season may be due to anthropogenic emissions transported by southwest monsoon from South Asia, as well as active bio‐metabolism and increasing local biogenic aerosol emissions (Zhang et al , ). However, the especially high wind speeds in the source region are likely responsible for the reversed AOD trend, as strong winds (from 3.5 to 5.0 m s −1 ) blowing from the northwest during dry seasons (especially spring) bring massive amounts of dust particles from Taklimakan Desert.…”
Section: Resultsmentioning
confidence: 99%